2021
DOI: 10.1007/s00403-021-02211-4
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma is associated with an increased risk of bullous pemphigoid: a large population-based longitudinal study

Abstract: The association between bullous pemphigoid (BP) and melanoma is yet to be investigated. We aimed to assess assess the bidirectional association between BP and melanoma and to delineate the epidemiological features of patients with both diagnoses. A population-based cohort study was performed comparing BP patients (n = 3924) with age-, sex- and ethnicity-matched control subjects (n = 19,280) with regard to incident cases of melanoma. A case–control design was additionally adopted to estimate the risk of BP in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…The fact that there were no differences in the overall malignancy rates between patients with BP and the general population is consistent with those of earlier studies, although inconsistent with those of others ( 14 19 ). Consistent with previous findings, the current study showed that patients with BP had a significantly higher rate of melanoma than that in the general population (10.7% vs 4.3%, respectively, p = 0.0005) ( 33 ). There are several suggested mechanisms underlying this association, including keratinocyte dysfunction and increased anti-BP230 autoantibodies, all of which have been observed in patients with melanoma, and human leukocyte antigen polymorphisms linked to both melanoma and BP (HLA-DQB1*03:01) ( 33 36 ).…”
Section: Discussionsupporting
confidence: 92%
“…The fact that there were no differences in the overall malignancy rates between patients with BP and the general population is consistent with those of earlier studies, although inconsistent with those of others ( 14 19 ). Consistent with previous findings, the current study showed that patients with BP had a significantly higher rate of melanoma than that in the general population (10.7% vs 4.3%, respectively, p = 0.0005) ( 33 ). There are several suggested mechanisms underlying this association, including keratinocyte dysfunction and increased anti-BP230 autoantibodies, all of which have been observed in patients with melanoma, and human leukocyte antigen polymorphisms linked to both melanoma and BP (HLA-DQB1*03:01) ( 33 36 ).…”
Section: Discussionsupporting
confidence: 92%
“…4,11 A population-level association between melanoma and BP has been recently reported; although the mechanism is unclear, contributing factors may include observed increased anti-BP antigen 2 (also known as BP180) autoantibodies among patients with melanoma and human leukocyte antigen variants associated with both melanoma and BP (HLA-DQB1*03:01). 12 Immune checkpoint inhibitor-induced immune activation may exacerbate this underlying preexisting risk. The roughly 2-fold discrepancy between the ORs for melanoma and NMSC may reflect differences in tumor biology that have yet to be ascertained, but these differences should be investigated in future translational work.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint inhibitor–induced BP has been previously reported in patients with melanoma and cutaneous squamous cell carcinoma who were treated with anti–PD-1 therapy . A population-level association between melanoma and BP has been recently reported; although the mechanism is unclear, contributing factors may include observed increased anti–BP antigen 2 (also known as BP180) autoantibodies among patients with melanoma and human leukocyte antigen variants associated with both melanoma and BP ( HLA-DQB1*03:01 ) . Immune checkpoint inhibitor–induced immune activation may exacerbate this underlying preexisting risk.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between PD-1/PD-L1-expressing B cells and PD-1+ follicular helper T cells facilitating humoral responses via B cell germinal centres are also being discussed as underlying mechanisms in ICI-BP (15)(16)(17). Contributing factors of altered expressions of BP180 in melanoma (18), aberrant immune response and genetic predisposition (HLA-DQB1*0301 for both melanoma and BP) appear to promote the loss of self-tolerance (19). In this study, we analysed a cohort of eight patients and characterized their BPassociated hemidesmosomal reactivity, along with the disease manifestations and treatment options for ICI-BP.…”
Section: Introductionmentioning
confidence: 99%